Social Market Economy in the context of the euro-crisis and as a feasible policy option - Resico, Marcelo Fernando (2015)
Fil: Resico, Marcelo Fernando. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina